2009
DOI: 10.1074/jbc.m109.015966
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Sequence-specific Recognition to DNA Modification

Abstract: Enzymes that modify DNA are faced with significant challenges in specificity for both substrate binding and catalysis. We describe how single hydrogen bonds between M.HhaI, a DNA cytosine methyltransferase, and its DNA substrate regulate the positioning of a peptide loop which is ϳ28 Å away. Stopped-flow fluorescence measurements of a tryptophan inserted into the loop provide real-time observations of conformational rearrangements. These long-range interactions that correlate with substrate binding and critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
25
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 20 publications
12
25
0
Order By: Relevance
“…Together, these structural alterations make the conformation of InC considerably more open at the interface between DNA and the catalytic domain than in ExC, and it is noteworthy that this opening results in partial disassembly of the active site in InC. These structural findings are thus consistent with the results of bio-chemical and biophysical studies on the closely related DCMTase M.HhaI, which showed that DNA binding precedes extrusion of the target nucleobase and initiation of catalysis (8,10,(27)(28)(29). Upon formation of the closed, catalytically active state, the mobile loops of the catalytic domain acquire multiple contacts to both the duplex DNA backbone (Ser-79, Arg-87, Arg-81, Lys-112, and Gln-117) and the extrahelical target cytosine (Gly-68 and Ser-75); these contacts are likely to stabilize the extrahelical, frameshifted conformation of the complex (compare Fig.…”
Section: Comparison Of the Structures Of Mhaeiii-dna Complexes Havinsupporting
confidence: 79%
“…Together, these structural alterations make the conformation of InC considerably more open at the interface between DNA and the catalytic domain than in ExC, and it is noteworthy that this opening results in partial disassembly of the active site in InC. These structural findings are thus consistent with the results of bio-chemical and biophysical studies on the closely related DCMTase M.HhaI, which showed that DNA binding precedes extrusion of the target nucleobase and initiation of catalysis (8,10,(27)(28)(29). Upon formation of the closed, catalytically active state, the mobile loops of the catalytic domain acquire multiple contacts to both the duplex DNA backbone (Ser-79, Arg-87, Arg-81, Lys-112, and Gln-117) and the extrahelical target cytosine (Gly-68 and Ser-75); these contacts are likely to stabilize the extrahelical, frameshifted conformation of the complex (compare Fig.…”
Section: Comparison Of the Structures Of Mhaeiii-dna Complexes Havinsupporting
confidence: 79%
“…Null or small fluorescence changes were detected when either the DNA or cofator was omitted from the reaction, indicating that the signal is dependent on the formation of the closed ternary complex (4,5,14). The fluorescence signal was also absent in the catalytically active W41F mutant, which contains no tryptophan residues (Supplementary Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…In all cases we used hemimethylated DNA to force one productive binding orientation; in the case of CcrM C. crescentus, the hemimethylated DNA is what the enzyme is normally presented with within the cell. We tested this first with M.HhaI, a structurally characterized DNA cytosine methyltransferase (methylates the underlined cytosines in 5Ј-GCGC-3Ј/5Ј-GCGC-3Ј) (15). As is typical for protein-DNA complexes, the M.HhaI-DNA cocrystal structure shows extensive interactions to bases within both strands, as well to the sugarphosphate backbone of both strands (16).…”
Section: Mismatched Dna Enhances Methylation By Ccrm C Crescentus Anmentioning
confidence: 99%